The Roles of Neuropeptide Y in Respiratory Disease Pathogenesis via the Airway Immune Response - Itano, Junko; Kiura, Katsuyuki; Maeda, Yoshinobu; Miyahara, Nobuaki (Acta medica Okayama, 2024)
The lungs are very complex organs, and the respiratory system performs the dual roles of repairing tissue while protecting against infection from various environmental stimuli. Persistent external irritation disrupts the immune responses of tissues and cells in the respiratory system, ultimately leading to respiratory disease. Neuropeptide Y (NPY) is a 36-amino-acid polypeptide and a neurotransmitter that regulates homeostasis. The NPY receptor is a seven-transmembrane-domain G-protein-coupled receptor with six subtypes (Y1, Y2, Y3, Y4, Y5, and Y6). Of these receptors, Y1, Y2, Y4, and Y5 are functional in humans, and Y1 plays important roles in the immune responses of many organs, including the respiratory system. NPY and the Y1 receptor have critical roles in the pathogenesis of asthma, chronic obstructive pulmonary disease, and idiopathic pulmonary fibrosis. The effects of NPY on the airway immune response and pathogenesis differ among respiratory diseases. This review focuses on the involvement of NPY in the airway immune response and pathogenesis of various respiratory diseases.